Webfólio: uma estratégia para a formação de enfermeiros - Miranda, Fernanda Maria de (Universidade Federal de São Carlos, 2016)
Considering the use of portfolios as a potential pedagogical strategy, as well as difficulties of implementation listed in the scientific literature and the resulting facilities of the digital world, this research was guiding question: The use of webfolio can be a powerful strategy to support construction the nursing students' knowledge? The aim of this study was to develop a minimum viable project, a webfólio, for nursing education and evaluate its technical quality with experts. It is an applied research and technological development, descriptive and exploratory nature. The collection and analysis of data was divided into two stages. In the first stage of the study were local teachers interviewed experienced in the use of reflective portfolios in order to understand the local reality as the use of reflexive portfolio and collect data to assist in the development of web-folio. Then, the conditions were set to be followed and the software has been developed, basing on the incremental development. The webfolio constituted, therefore, a web application in single page application with four levels of access. Possible among its activities minimum: user registration, disciplines, links to resize, reflective reports and fed back (in accordance with the permission of each user). The second data collection stage took place with experts from both computing as nursing faculty with experience with the use of reflective portfolios. The six inherent characteristics of software quality were evaluated. The functionality features, usability and efficiency were validated while the reliability characteristics, maintainability and portability require a reassessment with suggested improvements. The evaluation was considered positive by the subjects, especially the high acceptance of usability. The webfolio was seen as a powerful strategy to build the nursing students' knowledge, however, further studies with the implementation of webfolio developed into a real context will bring broader and more reliable results to corroborate this statement.
Webfolio: a strategy to nurse’s graduation.
Keywords: Informática em Enfermagem; Tecnologia Educacional; Aprendizagem; Nursing Informatics; Educational Technology; Association Learning; CIENCIAS BIOLOGICAS